Diurnal variation of HMG CoA reductase activity in rat intestine - S. Shefer; S. Hauser; V. Lapar; E.H. Mosbach (Journal of Lipid Research, 1972)
HMG CoA reductase activity of rat intestinal mucosa has a diurnal rhythm which coincides with the diurnal variation of the hepatic HMG CoA reductase but has a lower amplitude. The rhythmic variation of the intestinal reductase was present in both jejunal and ileal crypt cell microsomes and was not abolished by cholestyramine administration.